Prevalence and Antimicrobial Susceptibility of Multi-Drug Resistant Uropathogens in a Tertiary Hospital in Nepal: A One-Year Audit - Manish Man Pradhan; Sangita Sharma; Sujeet Poudyal; Diwas Gnyawali; Suman Adhikari; Suman Chapagain; Bhojraj Luitel; Hari Prasad Kattel; Pawan Raj Chalise (Journal of Nepal Medical Association, 2025)
Introduction: Antibiotic resistance, especially multidrug resistance, poses a global public health threat. It complicates the treatment of infections like urinary tract infections, leading to treatment failure, extended hospital stays, and increased healthcare costs. Empirical antibiotic therapy, guided by local resistance patterns, is crucial for patient outcomes and infection prevention. This study analyzes urine cultures from TU-Teaching Hospital from January to December 2024 to investigate the prevalence and antimicrobial susceptibility of multidrug-resistant uropathogens.